Sensitivity of precipitation extremes to radiative forcing of greenhouse gases and aerosols. Issue 18 (19th September 2016) - Lin, Lei; Wang, Zhili; Xu, Yangyang; Fu, Qiang
Abstract: Greenhouse gases (GHGs) and aerosols are the two most important anthropogenic forcing agents in the 21st century. The expected declines of anthropogenic aerosols in the 21st century from present‐day levels would cause an additional warming of the Earth's climate system, which would aggravate the climate extremes caused by GHG warming. We examine the increased rate of precipitation extremes with global mean surface warming in the 21st century caused by anthropogenic GHGs and aerosols, using an Earth system model ensemble simulation. Similar to mean precipitation, the increased rate of precipitation extremes caused by aerosol forcing is significantly larger than that caused by GHG forcing. The aerosol forcing in the coming decades can play a critical role in inducing change in precipitation extremes if a lower GHG emission pathway is adopted. Our results have implications for policy‐making on climate adaptation to extreme precipitation events. Key Points: The increased rate of precipitation extremes with global mean surface warming depends on the compositions of radiative forcing The increased rate of precipitation extremes with warming caused by aerosol forcing is significantly larger than that caused by GHG forcing Aerosol forcing in the coming decades can have a critical role in inducing change in precipitation extremes